Studies on the synthesis and reactivity of novel benzofuran-2-yl-[3-methyl-3-phenylcyclobutyl] methanones and their antimicrobial activity - Koca, M; Ahmedzade, M; Cukurovali, A; Kazaz, C (Mdpi, 2005)
Preparation in excellent yields of cyclobutyl benzofuran-2-yl- and naphthofuran-2-yl-ketones, the corresponding ketoximes and thiosemicarbazones, ether derivatives of the ketoximes and thiazoles derived from the thiosernicarbazones are described. Two of the synthesized compounds have been tested against eight different microorganisms and found to be active against some of the species studied.
Keywords: furans; cyclobutane; oxime; thiazole; thiosemicarbazone